MEDIATION OF ENTREPRENEURIAL INTENTIONS IN THE RELATIONSHIP BETWEEN ENTREPRENEURIAL TRAINING AND COMMUNITY BUSINESS LIFETIME - Nugraha, Deni; Ahman, Eeng; Disman; Mulyadi, Hari (Pena Cendekia Insani, 2025)
This study examines the effect of entrepreneurship training on the vitality of community businesses by considering the mediating role of entrepreneurial intentions in micro and small businesses in the culinary sub-sector in Cisitu, Darmaraja, Wado, Jatinunggal, and Jatigede Districts, Sumedang Regency. The study population included 984 culinary MSMEs, with a sample of 300 respondents. Data were collected through a survey method using a structured questionnaire and analyzed using Structural Equation Modeling (SEM) assisted by SmartPLS 4.1 software. The results showed that respondents rated entrepreneurship training, entrepreneurial intentions, and business viability as moderate (56.61%, 66.79%, and 49.26%), indicating a positive impact but still requiring strengthening. SEM-PLS analysis confirmed that entrepreneurship training had a positive and significant effect on business viability directly (path coefficient = 0.125; t-count = 2.333; p = 0.020) and on entrepreneurial intentions (path coefficient = 0.243; t-count = 4.015; p = 0.000). More importantly, entrepreneurial intentions were shown to significantly mediate the effect of training on business viability (indirect path coefficient = 0.049; t-count = 2.480; p = 0.013). This finding is supported by previous research that emphasized the importance of intentions as a mediator in the relationship between training and business sustainability.